Foreign trade and the national economy - Kindleberger, Charles P. (New Haven, Yale University Press, 1962)
The purpose of this volume is examine the economic function across a variety of national economies. It notes that if transport costs for goods were infinite and if consumers did not commute internationally there could be no international trade at all.
Includes index
Includes bibliography.
II 16/01/2019
Loans
Keywords: International trade; Economic conditions; Economic development